Device design principles and bioelectronic applications for flexible organic electrochemical transistors - Lin Gao; Mengge Wu; Xinge Yu; Junsheng Yu (International Journal of Extreme Manufacturing, 2023)
Organic electrochemical transistors (OECTs) exhibit significant potential for applications in healthcare and human-machine interfaces, due to their tunable synthesis, facile deposition, and excellent biocompatibility. Expanding OECTs to the flexible devices will significantly facilitate stable contact with the skin and enable more possible bioelectronic applications. In this work, we summarize the device physics of flexible OECTs, aiming to offer a foundational understanding and guidelines for material selection and device architecture. Particular attention is paid to the advanced manufacturing approaches, including photolithography and printing techniques, which establish a robust foundation for the commercialization and large-scale fabrication. And abundantly demonstrated examples ranging from biosensors, artificial synapses/neurons, to bioinspired nervous systems are summarized to highlight the considerable prospects of smart healthcare. In the end, the challenges and opportunities are proposed for flexible OECTs. The purpose of this review is not only to elaborate on the basic design principles of flexible OECTs, but also to act as a roadmap for further exploration of wearable OECTs in advanced bio-applications.